Teaching Chemical Engineering Thermodynamics using Substituted Blended Learning Techniques - Shafirah Samsuri; Wan Nur Aisyah binti Wan Osman (ASEAN Journal of Science and Engineering Education, 2024)
Blended learning was introduced to ensure students could navigate the complexities of Chemical Engineering Thermodynamics. Assessments in the form of summative, performance-based, and peer-and-self were applied to them. 80% of the students stated successful educators in facilitating blended learning excellently and giving adequate feedback on time. 76% of them mentioned their applicability in applying the knowledge from this course in daily life and industry scale. Furthermore, 72% of them indicated that they have a clear understanding of the aims and goals of this subject and can relate this subject with other subjects that they have learned. Moreover, the educator successfully conducted the course well by creating a conducive learning environment for student-educator interactions. Educators clearly explain all assessments to students very well and provide them with various resources to enhance their learning process. Hence, this blended learning is carefully mapped. The new learning approach in this course has brought positive outcomes toward the student's learning experiences, skills, and understanding.